Suplementos infantis de jornais : uma análise semiótica do gênero reportagem - Sousa, Luizete Adelaide da Pena de (2009)
Having the French Semiotic as a basis, this paper presents an analysis of reports published in children s supplements of Brazilian newspapers. The main objective is to contribute to the characterization of the report as a gender, as presented in newspapers aimed at children. This study analyzes the ge nder in the particular discursive modality of its implementation and considering the syncretic quality of the texts. Recurrences and reiterations examined allow to construct an invariant structure in children s supplements, which route sought to discover through the observation of themes and their figurative fulfillment s, the plan of expression and the marks left in the speech that identify people, time and space. Based on this invariant structure, it was possible to conclude that the gender report found in children's newspapers shows a strong relationship with the discourses of school and recreation, making the journalistic discourse less rigid than the pattern offered to adults in the visual organization of the page and in the written text. The survey results confirm that to identify and classify a gender, the text should be considered from the sense that Semiotic considers it: as the junction of the plan of the content and the plan of the expression.